BOBOT TETAS DAN FERTILITAS PADA AYAM KAMPUNG DAN HASIL PERSILANGANNYA - Herlina Herlina; La Ode Nafiu; Muhammad Amrullah Pagala (Universitas Halu Oleo, 2016)
This study aims to determine the performance of chicken and cross breeding results with laying hens and broilers. A total of 3 male chickens and 15 chickens Kampung females, 3 males laying chickens and 10 chickens laying females, and 3 chickens stud broiler. The variables observed were egg weight, fertility, hatchability, hatching weight. Data were analyzed with General Linear Model (GLM). Data on hatch weight, egg weight, fertility and hatchability were analyzed based on different breed. If there is a difference between treatments then a further test with Duncan Multiple Test is performed. The results showed that the performance of chicken and crossbreeding with laying and broiler chickens had significant effect (P <0,05) on egg weight, fertility, hatchability based on different nation and weight of hatch, body weight, heterosis and growth based on breed and different sex. Key Word : Performance, Crossbreeding, Kampung Chicken, Broiler, Layer.